Feeling or following? A field‐experiment comparing social norms‐based and emotions‐based motives encouraging pro‐environmental donations. Issue 4 (18th February 2020) - Bergquist, Magnus; Nyström, Lina; Nilsson, Andreas
Abstract: In this study, we design and explore interventions encouraging pro‐environmental donations by testing social norms and anticipated positive emotions. The social norms‐based intervention included descriptive and injunctive social normative information while the emotions‐based intervention included information about anticipated positive emotions. The two intervention techniques were tested in a field‐experiment; applying social norms‐based or emotions‐based messages to a real choice situation between retaining versus donating one's own money (i.e., using recycling machines giving people the choice to either retain money obtained from their recycled bottles, or to donate their money to a pro‐environmental organization). Results showed that more people donated their money after being exposed to the emotions‐based message, than the social norms‐based message or no message.